Preaching to the non-Muslim Chinese in Malaysia - Abdullah @ Chuah Hock Leng, Osman (IIUM Press, 2002)
This book is a study of the various barriers and difficulties in communicating the message of Islam to the non-Muslim Chinese in Malaysia and to find out the historical, political, economical, cultural differences between non-Muslim Chinese way of life and the Islamic way of life. It also analyzes the fears of Chinese and Malays in the ethnic relationship as minority and majority groups.